Dataset for "Instance dataset for a multiprocessor scheduling problem with multiple time windows and time lags: Similar instances with large differences in difficulty" - Karlsson, Emil (Linköping University, 2022)
Here lies the raw dataset for the publication "Instance dataset for a multiprocessor scheduling problem with multiple time windows and time lags: Similar instances with large differences in difficulty".

The following files and folders are made available here:
- [README.md](README.md). Describes the repository
- [instances](instances). Folder that contains the instances of the dataset (.zip files) together with files containing supporting information about instances (.txt files)
- [main.py](main.py). Main entry point for solving an instance with a Constraint Programming model
- [requirements.txt](requirements.txt). File containing the needed Python Packages to run the tests
- [LICENSE](LICENSE). File containing the License
- [data.py](data.py). Contains dataclasses that represents a problem definition
- [instance_io.py](instance_io.py). Contains methods for parsing instances from disc and writing instances to disc
- [cp_solve.py](cp_solve.py). Methods for creating a Constraint Programming model of the problem with IBM ILOG CP Optimizer
- [create_sbatch.py](create_sbatch.py). Entry point for creating sbatch files
- [sbatch](sbatch). Folder that contains SBATCH files for the instances in the dataset

The dataset was originally published in DiVA and moved to SND in 2024.
Dataset for "Instance dataset for a multiprocessor scheduling problem with multiple time windows and time lags: Similar instances with large differences in difficulty"
Keywords: instances; instances; time lags; time lags; avionics scheduling; avionics scheduling; exact time lags; exact time lags; multiple time windows; multiple time windows; multiprocessor scheduling; multiprocessor scheduling; constraint programming; constraint programming; instance dataset; instance dataset; Computational Mathematics; Beräkningsmatematik